2016
DOI: 10.1016/j.apjtm.2016.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Changes of adipocytokine expression after diabetic rats received sitagliptin and the molecular mechanism

Abstract: Sitagliptin can regulate the expression of adipocytokines in adipose tissue of diabetic rats through PI3K-AKT pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another significantly enriched pathway was the adipocytokine signaling pathway. Adipocytokines are a type of cytokines synthesized and secreted by adipocytes, and they have a regulatory effect on inflammation, insulin sensitivity, and endothelial function [ 70 , 71 ]. Three pathways, including the adipocytokine signaling pathway, were found to be significantly enriched (P < 0.05) for the targets of novel-mir-14 in the research of breast muscle in the Pekin duck [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another significantly enriched pathway was the adipocytokine signaling pathway. Adipocytokines are a type of cytokines synthesized and secreted by adipocytes, and they have a regulatory effect on inflammation, insulin sensitivity, and endothelial function [ 70 , 71 ]. Three pathways, including the adipocytokine signaling pathway, were found to be significantly enriched (P < 0.05) for the targets of novel-mir-14 in the research of breast muscle in the Pekin duck [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…From those mentioned mechanisms of SIRT1 and PTEN, the current study exhibited decreased of Akt‐p concentration in hepatic cells of HFD rats. Moreover adiponectin has a vital role in the insulin resistance pathway; it has a regulating influence on insulin sensitivity (Wu, Ni, & Lu, ). It was noticed that disturbance in lipid metabolism and excessive fat deposition leads to abnormal synthesis of adiponectin (Burnstock & Gentile, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover adiponectin has an important role in insulin resistance pathway; it is a member of adipocytokines which secreted by adipocytes and has a regulating effect on insulin sensitivity [40]. It was reported that disturbance in lipid metabolism and excessive fat deposition leads to abnormal synthesis of adipocytokines [41].…”
Section: Discussionmentioning
confidence: 99%